The association of burnout with work absenteeism and the frequency of thoughts in leaving their job in a cohort of healthcare workers during the COVID-19 pandemic - Lee, Cerina; Vu, Thanh-Huyen T.; Fuller, John A.; Freedman, Melanie; Bannon, Jacqueline; Wilkins, John T.; Moskowitz, Judith T.; Hirschhorn, Lisa R.; Wallia, Amisha; Evans, Charlesnika T. (Frontiers in Health Services, 2023)
During the coronavirus disease 2019 pandemic, high levels of burnout were reported among healthcare workers. This study examines the association of work absenteeism and frequency of thoughts in leaving current job with burnout among a cohort of healthcare workers during the COVID-19 pandemic. A cross-sectional survey of healthcare workers was conducted from April-May, 2022 on healthcare workers from 10 hospitals, 18 immediate care centers, and 325 outpatient practices in the Chicago area and surrounding Illinois suburbs. Logistic regression models were used to assess the association of burnout scores (Oldenburg Burnout Inventory -OLBI) and its sub-scores (exhaustion and disengagement scores) with work absenteeism and thoughts of leaving work. One-fifth and 60% of respondents (n=1,825) reported unplanned absenteeism and thoughts of leaving their job, respectively. After adjusting for covariates, higher burnout scores, especially exhaustion scores, were associated with increased odds of unplanned absenteeism (OR=1.04, 95% CI 1.01-1.08). Burnout scores and both sub-scores were also positively associated with the frequency of thoughts of leaving work, e.g., each unit increase in the OLBI burnout score was associated with 1.39 (95% CI 1.34-1.43) times higher odds of thinking about leaving work "a lot/constantly" vs. "never". More research is needed to support healthcare worker well-being during times of stress and direct solutions to addressing unplanned absenteeism in the light of a pandemic.